2011
DOI: 10.1111/j.1548-1492.2011.01128.x
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Identity: Academic Performance and Ethnic Identity among Ecuadorian Immigrant Teenagers in Madrid

Abstract: This article examines Ecuadorian students' attempts to contest immigrant stereotypes and redefine their social identities in Madrid, Spain. I argue that academic tracking plays a pivotal role in the trajectory of students' emergent ethnic identity. To illustrate this process, I focus on students who abandon their academic and professional ambitions as they are tracked into low‐achieving classrooms, and in the process participate in social and cultural practices that reify dominant stereotypes of Latino immigra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Cotterell 2007;Hey 1997) and, to some extent, in educational research (Lahelma 2002;Kehily et al 2002). Educational studies of migrants and minority ethnic youth have explored the impact of peers on achievement and attainment (Gándara, O'Hara, and Gutiérrez 2004;Ryabov 2009), and ethnographic research has looked at some of the ways in which school policies may affect inter-ethnic group relations (Lucko 2011;Pagani, Robustelli, and Martinelli 2011). In cross-national comparative research (usually quantitative), young people's friendships and social relations within schools are, however, largely absent, and even more so in studies of migrants and minority ethnic youth, which almost invariably focus on achievement and attainment.…”
Section: Contextualisation and Comparison Of Topics Identified By Resmentioning
confidence: 98%
“…Cotterell 2007;Hey 1997) and, to some extent, in educational research (Lahelma 2002;Kehily et al 2002). Educational studies of migrants and minority ethnic youth have explored the impact of peers on achievement and attainment (Gándara, O'Hara, and Gutiérrez 2004;Ryabov 2009), and ethnographic research has looked at some of the ways in which school policies may affect inter-ethnic group relations (Lucko 2011;Pagani, Robustelli, and Martinelli 2011). In cross-national comparative research (usually quantitative), young people's friendships and social relations within schools are, however, largely absent, and even more so in studies of migrants and minority ethnic youth, which almost invariably focus on achievement and attainment.…”
Section: Contextualisation and Comparison Of Topics Identified By Resmentioning
confidence: 98%
“…As educational research has shown, the system of academic tracking is also associated with inferior pedagogy and restricted educational and professional opportunities in the lower tracks, in which ethnic minority as well as working-class children and youths are heavily over-represented (Braddock and Slavin 1995;Gamoran et al 1995;Lucko 2011). For working-class students in Berlin, the apprenticeship diploma was the normative educational pathway until 2010 when a reform took place in the state.…”
Section: Introductionmentioning
confidence: 98%
“…In her qualitative study of Ecuadorean immigrant adolescents in Madrid, Lucko (2011) documented many of the obstacles the participants faced at school. They encountered, first of all, prejudice, embodied in stereotyping Latin American students as having limited academic ability.…”
Section: Introductionmentioning
confidence: 99%
“…Many teachers expected all Latin American pupils to proceed to the non-academic tracks that are very distinct from the academic tracks of Spanish schools. Lucko (2011) found that once placed in the non-academic tracks, they tended to befriend other Latin American immigrants who were disillusioned with the educational system and who did not make academic achievement a priority. With specific regard to adolescent immigrants, Briones, Verkuyten, Cosano, and Tabernero (2012), focusing on two large immigrant groups, Moroccan and Ecuadorian, found that identification with the Spanish host culture was positively linked in general with psychological well-being in terms of self-efficacy and life satisfaction.…”
Section: Introductionmentioning
confidence: 99%